2010
DOI: 10.1007/s00134-010-1832-6
|View full text |Cite
|
Sign up to set email alerts
|

APACHE-II score and Killip class for patients with acute myocardial infarction

Abstract: APACHE-II score and Killip class are useful for assessing the severity of patients with AMI and are complementary. Each can be used with a few commonly gathered clinical variables to construct prognostic models to assess severity. Their joint application yields a model with excellent discrimination capacity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 37 publications
1
13
1
Order By: Relevance
“…22 Recently, the same group found that a prognostic model that included the Killip classification and APACHE II showed good accuracy. 24 Our study was the first one to compare the performance of two recent general scores (APACHE IV and SAPS 3) and one specific ACS score (GRACE). SAPS 3 demonstrated poor calibration, which may have been due to inappropriateness for assessing an ACS population or to different clinical presentation and treatment choices in this specific population.…”
Section: Discussionmentioning
confidence: 99%
“…22 Recently, the same group found that a prognostic model that included the Killip classification and APACHE II showed good accuracy. 24 Our study was the first one to compare the performance of two recent general scores (APACHE IV and SAPS 3) and one specific ACS score (GRACE). SAPS 3 demonstrated poor calibration, which may have been due to inappropriateness for assessing an ACS population or to different clinical presentation and treatment choices in this specific population.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous published article, we analyzed the prognostic value of Killip and APACHE II systems in ST-elevation myocardial infarction (STEMI); the 2 systems identified as being complementary and useful for assessing the severity of AMI [22]. Moreover, we observed that Killip classification, age, and sex were able to distinguish prognostic groups within STEMI patients.…”
Section: Introductionmentioning
confidence: 85%
“…We have selected variables based on the findings in the univariable analysis of this study, previous studies we had carried out [22] and existing literature. For ease of interpretation and later use of the findings in our study, we have classified the age variable following the example of previous authors [27].…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, "shortness of breath" can be considered a surrogate for heart failure and/or myocardial infarct size. In fact, it has been demonstrated that increased Killip class was associated with poorer outcome (8,9). Jabbari et al identified Killip class > 1 at admission as a predictive factor of ventricular fibrillation (VF) before primary percutaneous coronary intervention in patients with STEMI (7).…”
Section: Editorialmentioning
confidence: 99%